(3JhVjM GdJPcQI ` aj Yde GdgjFIs - (3GdMSf Hf eMeO Hf GdMSjf Gdbej GdfjSGHhQqi, fXGe GdOjf, hjbGd dg GdCYQL ` HYO (B850 (3g` s; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s
(3ChdgG (B:s
(3deG PcQ Gf dcd Yde ehVhYkG HeHGOF heSGFd TQYjI abhdg GdCLQGe jYfi Ydi Cf GdBNQ eGdjS HCLQGe cGdYbhd s
(3BNQgG (B:s
(3aEf GdCYeGd HGdfjGJ , hHgG JLdH GdHQcGJ , hJfGd GdOQLGJ , hGdMeO ddg deHOY Gdcd hbO EJab aQGZi ef JCdja gPG GdcJGH s
(3HgG fXGe GdJYbjHIs
(3HgG CTcGd hQShes
(3fSNI NGeSIs
(3JJab ai BNQgG eY BNQ GdfSNI GdChdi HGNJdGa jSjQ ai HYV GdCdaGX s
(3cJHJ Hbde eged GdfbW cKjQkG s
(3fSNJ ai MjGI GdeDda s
Keywords: (3Gdadcs